Cardiac left ventricular thrombus in protein C deficiency - Sabzi, Feridoun (Medknow Publications & Media Pvt Ltd, 2014)
We report an exceptional case of, 33-year-old woman presenting with, dyspnoea and chest pain, Cardio respiratory sign and symptom related to diastolic dysfunction caused by mass effect of thrombosis on diastolic filling of left ventricule (LV). The common aetiologies of these devastating complication results in thrombophillia diagnosis, and echocardioghraphy showed a large mass in left ventricular cavity. In laboratory exam, protein C-S deficiency was confirmed however, others related test of thrombophillia were negative. The patient underwent cardiopulmonary bypass with thrombosis extraction and her sign and symptom, recovered uneventfully. This case report illustrates an exceedingly rare case of thrombophilia-induced left ventricular clot formation.